Assessment of the program for use of the monoclonal antibody palivizumab in Sao Paulo State, Brazil - Goncalves, Ivana Regina [UNESP]; Carvalho Nunes, Helio Rubens de [UNESP]; Cassamassimo Duarte, Marli Teresinha [UNESP]; Garcia de Lima Parada, Cristina Maria [UNESP] (Cadernos Saude Publica, 2018)
This study aimed to assess the program for use of the monoclonal antibody palivizumab in Sao Paulo State, Brazil. The evaluation adopted the frame of reference proposed by Donabedian, and the data were discussed on the basis of the guidelines from the Ruling on the use of palivizumab in the national network and in the Manual on Standards and Procedures for Vaccination. Sixteen application services in the state were included, with 693 children/mothers enrolled in the program in 2014 (85.1% of the eligible population). For the structure and process evaluation, scores were created that allowed classifying the application services as adequate, partially adequate, and inadequate (non-compliance rates were <= 10%, 11-20%, and > 20%, respectively). Results were evaluated according to the association between failure to administer palivizumab and need for hospitalization due to respiratory disease/symptoms, based on the point and interval odds ratios, with 95% confidence interval and critical p-value < 0.05. Of the 11 application services whose structure was classified as adequate, only two showed adequate process, four showed inadequate process, and five partially adequate process. Risk of ICU admission due to respiratory disease/symptoms increased on average by 30% for each failure (p = 0.003; OR = 1.30; 95% CI: 1.09-1.55). In conclusion, having a favorable structure for the program for use of palivizumab in Sao Paulo State did not necessarily result in an adequate process. In general, the situation with the structure was better than the process. All doses of the monoclonal antibody need to be administered in order to prevent hospitalization from respiratory disease/symptoms.
Keywords: Palivizumab; Immunoglobulins; Passive Immunization; Risk Groups; Program Evaluation